Réponses

  • Utilisateur Brainly
2014-09-03T18:31:14+02:00
Ex 2 :
a)
7 x 3 = 21
8 + 6 = 14
(4 + 7) x 5 = 11 x 5 = 55
6 x 3 + 2 = 18 + 2 = 20
4 x 8 + 5 x 3 = 32 + 15 = 47

b) 
A= 5 + 3 x 6 = 5 + 18 = 23
B= 7 x 8 - 3 x 5 = 56 - 15 = 41
C= 6 x 8 + 12 = 48 + 12 = 60
D= 12 + 8 : 2 = 12 + 4 = 16
E= 5 x (3 + 9) = 5 x 12 = 60
F= (3 + 4 x 5) x 2 = (3 + 20) x 2 = 23 x 2 = 46

Ex 3 :
A= (+ 6) + (- 8) = 6 - 8 = - 2
B= (+ 11) + (- 7) = 11 - 7 = 4
C= (- 6) + (- 8) = - 6 - 8 = - 14
D= (+ 8) - (+ 12) = 8 - 12 = - 4
E= (+ 5) - (- 9) = 5 + 9 = 14
F= (- 7) - (- 4) = - 7 + 4 = - 3
G= - 5 - 3 = - 8
H= - 6 + 4 = - 2
I= + 8 - 12 = - 4
J= (- 6) + (+ 12) + (+ 4) + (- 8) = - 6 + 12 + 4 - 8 = 16 - 14 = 2
K= (- 7) - (- 4) + (- 6) - (+ 8) + (+ 5) = - 7 + 4 - 6 - 8 + 5 = 9 - 21 = - 12
L= 15 - 8 + 2 = 17 - 8 = 9
M est illisible.. :/
N= - 23 + 79 + 23 - 16 + 12 - 79 = - 23 + 23 - 79 + 79 - 16 + 12 = 12 - 16 = - 4
M = -9 - 8 - 6
M = -23
Effectivement avec des bons yeux, merci ! :)
merci
2014-09-03T19:14:58+02:00
Exercice 2 :
a)
(1) 7 x 3 = 21 (produit)
(2) 8 + 6 = 14 (somme)
(3) (4 + 7) x 5 = 11 x 5 = 55 (somme et produit)
(4) 6 x 3 + 2 = 18 + 2 = 20 (produit et somme)
(5) 4 x 8 + 5 x 3 = 32 + 15 = 47 (produit somme produit)

b)
A = 5 + 3 x 6
A = 5 + 18
A = 23

B = 7 x 8 - 3 x 5
B = 56 - 15
B = 41

C = 6 x 8 + 12
C = 48 + 12
C = 60

D = 12 + 8 : 2
D = 12 + 4
D = 16

E = 5 x (3 + 9)
E = 5 x 12
E = 60

F = (3 + 4 x 5) x 2
F = (3 + 20) x 2
F = 23 x 2
F = 46

Exercice 3 :

a)
A = (+ 6) + (- 8)
A = 6 - 8
A = - 2

B = (+ 11) + (- 7)
B = 11 - 7
B = 4

C = (- 6) + (- 8)
C = - 6 - 8
C = - 14

b)
D = (+ 8) - (+ 12)
D = 8 - 12
D = - 4

E =  (+ 5) - (- 9)
E = 5 + 9
E = 14

F = (- 7) - (- 4)
F = - 7 + 4
F = - 3

c)
G = - 5 - 3
G = - 8

H = - 6 + 4
H = - 2

I = + 8 - 12
I = - 4

d)
J = (- 6) + (+ 12) + (+ 4) + (- 8)
J = - 6 + 12 + 4 - 8
J = - 6 - 8 + 12 + 4
J = - 14 + 16
J = 2

K = (- 7) - (- 4) + (- 6) - (+ 8) + (+ 5)
K = - 7 + 4 - 6 - 8 + 5
K = - 7 - 6 - 8 + 4 + 5
K = - 21 + 9
K = - 12

e)
L  = 15 - 8 + 2
L = 17 - 8
L = 9

M  = - 9 - 8 - 6
M = - 23

N = - 23 + 79 + 23 - 16 + 12 - 79
N = - 23 + 23 - 79 + 79 - 16 + 12
N = - 16 + 12
N = - 4